The Influence of Organizational Development and Human Resources on the Effectiveness of Marine Corps Territorial Staff Duties - Hana Prasetyaji; Yuni Pratikno; Sitta Kusuma (Dinasti International Journal of Digital Business Management, 2026)
Personnel work effectiveness is a crucial factor in supporting the successful implementation of military organizational tasks and functions, especially in the Marine Corps Territorial Staff which has a strategic role in fostering regional potential and empowering the defense community. This study aims to analyze the influence of Organizational Development and Human Resource Development on the Work Effectiveness of Marine Corps Territorial Staff Personnel, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data collection was carried out by distributing questionnaires to 93 Marine Corps territorial staff personnel who were used as research respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that partially Organizational Development has a positive and significant effect on Personnel Work Effectiveness, with a t-value of 3.525 and a significance level of <0.001. In addition, Human Resource Development also has a positive and significant effect on Personnel Work Effectiveness, with a t-value of 5.498 and a significance level of <0.001. Simultaneously, Organizational Development and Human Resource Development have a significant effect on Personnel Work Effectiveness, as indicated by the F-value of 22.514 with a significance of <0.001. The coefficient of determination (R Square) of 0.333 indicates that the two independent variables are able to explain 33.3% of the variation in Personnel Work Effectiveness, while the rest is influenced by other factors outside the research model. This finding confirms that strengthening planned organizational development and continuously improving the quality of human resources are strategic factors in increasing the effectiveness of the Marine Corps Territorial Staff's duties